Spontaneous Pregnancy after 4D-Hysterosalpingo-Sonography (HyCoSy) in the Same Menstrual Cycle: A Case Report and an Updating Review of the Current Literature regarding the Positive Impact of Tubal Flushing Effect on Fertility - Francesco Bisogni; Francesco Galanti; Serena Riccio; Simona Ghanitab; Stefania Polletta; Valentina Annesi; Domenico Antonaci; Andrea Rago; Michele Carlo Schiavi; Vincenzo Spina; Rocco Rago (Hindawi Limited, 2024)
Infertility is increasing worldwide, as well as in Italy, and fallopian tube pathology represents one of the most impacting causes of infertility for multiple women. Indeed, tubal patency assessment is a crucial step in medical evaluation for women attending an in vitro fertilization (IVF) center. Currently, different methods for tubal investigation are available, such as chromosalpingoscopy, hysterosalpingography (HSG), and hysterosalpingo-contrast sonography (HyCoSy). This diagnostic exam is performed by ultrasonography and an air-water-based contrast agent represented by air-water, or foam solution (HyFoSy). An additional side benefit of these assessment tests is a fertility-enhancing effect, thanks to a positive effect defined as "tubal flushing," which in current literature is more strongly associated with HyFoSy with respect to HyCoSy. In this report, we present a case of a 34-year-old woman presented to our attention at the Reproductive and Physiopathology Unit of Sandro Pertini Hospital, Rome, in 2023, with unexplained infertility for 3.1 years of free sexual intercourse with a partner who did not report sperm abnormalities. Subsequently, in this exam, the woman spontaneously conceived in the same menstrual cycle that the 4D-HyCoSy was performed, without any additional fertility enhancement interventions. In this case report, we also include an updating review of the current literature regarding the insurgence of spontaneous pregnancy after this technique in order to explore the physiopathological and etiopathogenetic mechanisms underlying the achievement of spontaneous pregnancy and to confront our case with other recent works published. According to our clinical experience and the current literature, 4D-HyCoSy is the easiest, safest, and cheapest diagnostic exam for investigating tubal patency, which can lead to medical success in some cases of "unexplained infertility" as the achievement of a spontaneous pregnancy.